Communication emotional strategies in media political discourse - Pałuszyńska, Edyta (Papers in Linguistics, 2019)
The aim of the article is to examine how the colloquial image of emotions, which is in the social consciousness, is used strategically in political discourse. Important elements of this image include: opposing emotions to reason, spontaneity, truthfulness, violence. I define emotional strategy as a kind of deliberate and deliberate action that instrumentally uses knowledge about the social rules of expressing emotions and reading or interpreting signs of emotions in order to persuasively construct a communication situation. The research material were recordings of the "Morning Radio of the Radio Tok FM" broadcast from April 1, 2017 to March 30, 2018. The analytical part contains examples of emotional strategies, along with a discussion of their mechanisms and effects.